Anti-money laundering handbook - Deitz, Alison [ (Alison Joy)] , 1961-; Buttle, John [ (John Robert)] , 1953- (Thomson/Lawbook Co., 2008)
"This Handbook is both for those having to comply with the Anti Money Laundering (AML) and Counter Terrorism Financing Reforms and for their advisors. The work translates the complicated legislative package into a clear and accessible tool designed to be used at each stop of the implementation of the business?s AML strategy. The book is broken up into 6 parts and includes the IFSA Guidelines. Part A: International money laundering and terrorisim financing countermeasures, laws and standards Part B Australian money laundering and terrorism financing laws and counter measures Part C Establishing and maintaining successful AMLICTF systems and controls Part D Enforcement Part E Industry chapters Part F Glossary IFSA Guidelines Index."--Provided by publisher